2019
DOI: 10.5552/drvind.2019.1821
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mat layers moisture content on some properties of particleboard

Abstract: In this study, the effect of mat moisture content on the physical and mechanical properties of particleboard was investigated. The experimental boards were produced by using 40 % softwood, 45 % hardwood chips, and 15 % sawdust. The formaldehyde resin/adhesive was used in three-layers (bottom-top layer 12 %, core layer 8 %). Multi-opening press was used during manufacturing the experimental particleboards. The physical and mechanical properties of boards obtained were identified according to the TS-EN standards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…When the MC of the mat was reduced by changing the oven temperature from 80 to 100°C, the WA increased by about 20% after 24 hours of immersion. Previous studies have also shown that deviation from the optimal MC in the mat has a negative effect on the WA of particleboard (Istek et al, 2019). The accumulation of vapor in the core layer (high MC of the mat) and the weakening of the heat transfer process in the core (low MC of the mat) were the main factors affecting the intensity of adhesive curing, which also affects the WA of the specimens.…”
Section: Physical Propertiesmentioning
confidence: 90%
“…When the MC of the mat was reduced by changing the oven temperature from 80 to 100°C, the WA increased by about 20% after 24 hours of immersion. Previous studies have also shown that deviation from the optimal MC in the mat has a negative effect on the WA of particleboard (Istek et al, 2019). The accumulation of vapor in the core layer (high MC of the mat) and the weakening of the heat transfer process in the core (low MC of the mat) were the main factors affecting the intensity of adhesive curing, which also affects the WA of the specimens.…”
Section: Physical Propertiesmentioning
confidence: 90%
“…Their results are therefore obscured by parameters that have well-known influences on board properties. These are board density [4][5][6], distinctive density profile [7], multi-layered board structure (different particle sizes in face and core layer), obvious particle-size distribution perpendicular to the board plane, adhesive content (AC) [3] (pp. 786-789), and surface-specific adhesive amount (SSAA) [2].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Istek et al [8] investigated three-layer particleboards with varying particle dimensions in the face and core layers by using different sieve fractions. Due to the production parameters (press temperature: 180 • C; press duration: 190 s), it is likely that the boards possess distinctive density profiles that vary with the applied particle material and thus obscure the influence of the particle size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physicomechanical properties of particleboards, except their technological parameters, depend significantly on the characteristics of the raw materials used in their production [ 1 ]. These are the type and amount of the adhesive system used for their bonding, the type of the raw material, its degree of fragmentation and geometry (size and shape), and moisture content [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. The right choice of the moisture content of the particles, independently of their fineness degree, is also necessary for assuring the correct industrial process of particleboards.…”
Section: Introductionmentioning
confidence: 99%